PENGEMBANGAN KREATIVITAS TARUNA/I MELALUI KEGIATAN EKSTRAKURIKULER DALAM LINGKUP SEKOLAH KEDINASAN - Sukarwoto Sukarwoto; Muhammad Caesar Akbar; Gerald Christ Mario Hutabarat (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to carry out the development of creativity in cadets through extracurricular activities at the Medan Aviation Polytechnic. This research is a descriptive study with a qualitative assessment. The selection of subjects for this study were several extracurriculars at the Medan Aviation Polytechnic. Data analysis was carried out by going through the stages of data collection, data reduction, data display and verification as well as drawing conclusions. The data validity test was carried out using source and method triagulation. And for this reason, the authors are interested in studying and researching the Development of Youth Creativity through Extracurricular Activities within the scope of Service Schools. This type of research is a qualitative method. Data collection is carried out using interviews, observation, and documentation which is supplemented by a list of questions. The results of the study show that the development of creativity at the Medan Aviation Polytechnic carried out by trainers through creativity development programs through extracurriculars is intended to help cadets to be better potential and personally. This activity is intended to develop the creativity of cadets so that cadets can channel their interests and talents and increase their self-confidence to socialize. The process of developing creativity is carried out in line with the stages of its development, including awareness and formation of behavior through discussion with a personal approach. The discussion or sharing was chosen by the extracurricular trainers to raise awareness because they found that one group of cadets tended to be more volatile than other groups. The second stage of the ability transition is in the form of an overview of the knowledge and skills realized by the trainers by conducting socialization. In addition, the provision of extracurricular skills and creativity is carried out 2-3 meetings regularly after school hours by lecturers. The third stage is capacity building by participating in competitions to have the courage to appear in society or other agencies.